Advantages and disadvantages of line and staff style of organizations - Omolaja, Muhammad (International Review, 2015)
In the paper we discussed the fact that the dichotomous concepts of modernorganizations exist in reality. We are focused on line and staff style of organizationsbecause they are closely knitted. In line with this, their difference might not be easilyidentified by the laymen in organizational analysis and management. So, the main aim ofour paper was to identify certain benefits from the knowledge of line and stafforganizational analysis for modern managers as well as for employed people in anorganisation. In the paper is concluded that the degree or extent of complexity,dependability, stability and adaptability of the technology and techno-structure of anorganization will naturally dictate the way and manner the operations of the enterprise aredistributed. By implication, the technology of an enterprise always dictates its span ofcontrol authority levels and extent of delegation, responsibility assignment, and number ofsteps along the ladder of responsibilities.